PENGGUNAAN RODA PINTAR UNTUK KEMAMPUAN MEMBACA ANAK - Redina Simbolon (Universitas Pakuan, 2019)
THE USE OF SMART WHEELS FOR THE ABILITY TO READ CHILDRENWas used in the study of a wheel smart. A wheel smart is one of medium used to have been used to simplify the son of in reading. In the wheels of smart there are a board where the board first there are vowels, board second there are letters konsinan, and board third there are syllables. In a wheel smart later on can develop the ability the son of bank notes the nepali language, not only in a working meeting with about the concept of developing found herself listening to have been ready for speaking, read and write. Excess of media wheels smart this is easy and there are elements used game so students the joy of learning while playing. Using the smart are the expected to read well. Its objective in reading is so acquisition reading comprehension, Includes the contents of, and understand the meaning contained in reading materials. By reading someone be able to widen insight and knowledge. Methods used in this study this research is qualitative research methodology descriptive. Technique use the theory of data collection study experts taken of some books and scientific journal. The action used in this research was media uses the smart.